IMPLEMENTATION OF PRINCIPLES OF STRATEGIC COMMUNICATIONS IN FORMING A POSITIVE IMAGE OF A GOVERNMENT BODY - Ninyuk, Inna; Larina, Nataliia; Ninyuk, Mariya (Public Management and Policy, 2025)
A special role in modern social development strategies is given to the communication support of public administration processes. which will enable increasing the effectiveness of anti-corruption policy and intensifying relations between the authorities and civil society. The purpose of the article is to analyze the specifics of the implementation of the principles of strategic communications in the formation of a positive image of a state authority. The study determines the priority functions of communication in the system of public administration – the formation of a positive image and public awareness. The article considers the features of the formation of a positive perception of government in the eyes of citizens on the basis of transparent, two-way and consistent communication with the public, adherence to ethical standards and strengthening public trust. The main approaches to defining the phenomenon of “image” and positioning it as an effective channel of communication are summarized. The emphasis is on the role of public opinion in the context of feedback in the communicative activities of a state authority. The key directions of forming a positive image of state authorities and increasing the level of public trust in them based on the use of the potential of strategic communications are identified. Within the framework of the article, the phenomenon of strategic communications is considered in the context of a means of assimilating aspects of organizational activity, transformational changes and behavior modification, implementing the primary goals of public authorities and increasing the effectiveness of the information narrative. The analysis of the main concepts of strategic communication made it possible to establish that establishing a productive dialogue between state authorities and civil society requires the integration of a systematic and purposeful concept, within which decisions made by state authorities should be based not only on the personal experience of leaders, but also on the results of public opinion analysis, priority scientific positions, modeling and forecasting of social dynamics, with the general direction of achieving maximum coordination between the public and the state authority. This will strengthen the positive image of power formations and ensure an unhindered system of citizen participation in socio-political life.